ANALISIS KESIAPAN IMPLEMENTASI IFRS S1 DAN S2 PADA INDUSTRI NIKEL DI INDONESIA: STUDI KASUS PT ANTAM Tbk - Febria Agatha Br Sembiring; Rani Agustini; Seraya M Sinaga; Steven Jonathan Parsaoran Pasaribu; Nur Intan Mei Hidayati (Komunitas Manajemen Kompetitif, 2026)
The adoption of global standards IFRS S1 and IFRS S2 requires companies to enhance transparency by directly linking sustainability and climate risks to financial performance. This study aims to evaluate the readiness of PT ANTAM Tbk, a strategic entity in Indonesia's nickel industry, in adopting these reporting standards. This study employs a qualitative descriptive method with content analysis of the 2024 Sustainability Report. The assessment instrument utilizes a checklist comprising 29 disclosure indicators covering four pillars: Governance, Strategy, Risk Management, and Metrics and Targets. The results indicate that PT ANTAM Tbk is in the